Lung cancer in Teesside (UK) and Varese (Italy): a comparison of management and survival. Issue 3 (11th November 2005) - Imperatori, A; Harrison, R N; Leitch, D N; Rovera, F; Lepore, G; Dionigi, G; Sutton, P; Dominioni, L
Abstract : Background: The survival of lung cancer patients in the UK is lower than in other similar European countries. The reasons for this are unclear. Methods: Two areas were selected with a similar incidence of lung cancer: Teesside in Northern England and Varese in Northern Italy. Data were collected prospectively on all new cases of lung cancer diagnosed in the year 2000. Comparisons were made of basic demographic characteristics, management, and survival. Results: There were 268 cases of lung cancer in Teesside and 243 in Varese. Patients in Teesside were older (p<0.05), were more likely to have smoked (p<0.001), had a higher occupational risk (p<0.001), higher co-morbidity (p<0.05), and poorer performance status (p<0.001). Fewer patients in Teesside presented as an incidental finding (p<0.001) and the histological confirmation rate was lower than in Varese (p<0.01). In Teesside there were more large cell carcinomas (p<0.001), more small cell carcinomas (p<0.05), and fewer early stage non-small cell lung cancers (p<0.05). The resection rate was lower in Teesside (7% v 24%; p<0.01) and more patients received no specific anti-cancer treatment (50% v 25%; p<0.001). Overall 3 year survival was lower in Teesside (7% v 14%; p<0.001). Surgical resection was the strongest multivariate survival predictor in Varese (HR = 0.46) and Teesside (HR = 0.31). Co-morbidity in Teesside resulted in a significantly lower resection rate (p<0.001). Conclusions: Patients with lung cancer in Teesside presented at a later stage, with more aggressive types of tumour, and had higher co-morbidity than patients in Varese. As a result, the resection rate was significantly lower and survival was worse.